Peranan Kualitas Layanan dan Harga Dalam Meningkatkan Kepuasan Pelanggan PT. Balina Agung Perkasa - Irpan Saepuloh; Widiana Indah Permata (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
This study aims to determine the Role of Service Quality and Price in Increasing Customer Satisfaction of PT. Balina Agung Perkasa. This research uses descriptive qualitative research methods. The informants in this study were 8 informants who were customers of PT. Balina Agung Perkasa and owned a shop. The data collection methods used are observation, interviews, and documentation. The data collected were analyzed descriptively by reducing data, presenting data, and drawing conclusions. The results of research conducted by conducting interviews show that the Role of Service Quality and Price in Increasing Customer Satisfaction of PT. Balina Agung Perkasa is very good as evidenced by every purchase of an item or product, PT. Balina Agung always provides products according to customer demand, PT. Balina Agung Perkasa is very responsive to customers, PT. Balina Agung Perkasa provides excellent guarantees to customers, customers always receive empathy from PT Balina Agung Perkasa such as attention and care. Balina Agung Perkasa such as attention and care, tangible owned by PT. Balina Agung Perkasa is very good, the products sold at PT. Balina Agung Perkasa have a very affordable selling price, the selling price of PT. Balina Agung Perkasa is very competitive in the market, the selling price of the product with the quality of the product is appropriate, and PT. Balina Agung has a price that is in accordance with the benefits of the products provided to customers. Keywords: Service Quality, Price, Customer Satisfaction